Compare the Histological Features between the Normal and Hypertensive Placenta - Atif Hussain, Nazma Kiran, Nida Qasim Hayat, Sadaf Shaheen, Abdul Hafeez Baloch, Abdul Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of the current research was to investigate the morphology and histology of placentas collected from moms who had PIH and to compare those results to placentas taken from women who had normal pregnancies. Study Design: The study was conducted at Anatomy department of Women Medical and Dental College Hospital Abbottabad and Mohi-ud-Din Islamic Medical College, Mirpur, AJK during the period from February 2021 to July 2021. Place and Duration: Observational/comparative study Methods: In this study total 80 pregnancies, 40 normal placenta’s and 40 hypertensive placenta’s were presented. At first, the physical aspects of placentas, also known as their morphological traits, were noted. In order to investigate the histology, pieces of each placenta measuring 5 millimetres in thickness were removed. After this, the tissue underwent further histological processing, after which it was fixed in formal saline at a concentration of 10 percent. It was noted down how much newborns weighed at birth. SPSS 23.0 was used to analyze complete data. Results: Placental weight, size, surface area and number of cotyledons were decreased in hypertensive placentas, whereas regions of infarction, retroplacental clot, and calcification were increased. Hyalinized villi and atherosclerosis have been reported in hypertensive placentas (p0.05). Foetal mortality and morbidity were closely linked to these alterations. We also found that among women with high blood pressure who had the aforementioned histological alterations in their placentas, the risk of foetal death and morbidity was higher. Conclusion: We concluded that, PIH reduces placenta weight and size. Changes in utero-placental blood flow may induce placental insufficiency. It affects newborn birth weight. PIH impacts placenta shape, histology, and foetal development.